(3eHGOF CQGA Cgd GdeOjfI GdaGVdIs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3GMUGA GdGHhGH GdJi ai eNJUQ cJGH GdeOfi GdChd gh SHH dhLhO SGFQ GdehLhOGJ cdgG hghHQF ef LejY GfMGA GdfbU s
(3BNQgG (B:s
(3jLYd GdGTjGA cdgG eecfI Gf jhLO ai LhGgQgG hLhOGJ eJbGHdI hhLhOGJ HdG fgGjI ai LhGgQgG hGYQGVgG Je GdcJGH HYhf QH GdGHGH s
(3Vef eLehY , JQJjHgG (B: (3GdKGfi YTQs
(3GdfSNI HgG MhGTs
(3GfXQg eY GdeNWhW Qbe (B305 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B52s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs